2014
DOI: 10.1145/2555595
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Search and Browsing Behavior of Young Users on the Web

Abstract: The Internet is increasingly used by young children for all kinds of purposes. Nonetheless, there are not many resources especially designed for children on the Internet and most of the content online is designed for grown-up users. This situation is problematic if we consider the large differences between young users and adults since their topic interests, computer skills, and language capabilities evolve rapidly during childhood. There is little research aimed at exploring and measuring the difficulties that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 73 publications
0
31
0
Order By: Relevance
“…A substantial body of research has documented the obstacles children face when formulating search queries and identifying appropriate results (e.g., Foss et al, 2012; Gossen, Höbel, & Nürnberger, ; Duarte Torres, Weber, & Hiemstra, ; Madrazo Azbiazu, Dragovic, Anuyah, & Pera, ). For instance, an analysis of Yahoo!…”
Section: Children's Understanding and Use Of Online Information Searchesmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial body of research has documented the obstacles children face when formulating search queries and identifying appropriate results (e.g., Foss et al, 2012; Gossen, Höbel, & Nürnberger, ; Duarte Torres, Weber, & Hiemstra, ; Madrazo Azbiazu, Dragovic, Anuyah, & Pera, ). For instance, an analysis of Yahoo!…”
Section: Children's Understanding and Use Of Online Information Searchesmentioning
confidence: 99%
“…For instance, an analysis of Yahoo! search queries and web behavior among children ages 6–7, 8–9, and 10–12 revealed that younger children's searches lasted for a shorter time than older children's searches, and that younger children typed in shorter queries (i.e., fewer terms in the search bar), and were more likely to use natural language (i.e., phrasing queries in the form of a question), which can be problematic for some search engines (Duarte Torres et al, ). They were also more likely to undo auto‐corrections by the search engine and to click on whatever item or link was most prominent in the search results, even if it was an advertisement.…”
Section: Children's Understanding and Use Of Online Information Searchesmentioning
confidence: 99%
“…al. [37] employed toolbar logs from a commercial search engine to characterize the browsing behavior of young aged users, particularly for understanding the activities on the Internet that trigger search activity. The proportion of browsing and search activity in the toolbar sessions estimated the likelihood of a user to carry out search on the Web vertical and multimedia verticals (i.e.…”
Section: Demographic User Modelingmentioning
confidence: 99%
“…Second, there is substantial potential for leveraging speech interfaces to address a number of challenges that children face with current text-based search practices. Log analysis has found that children's web searches are frequently "unsuccessful" and "confused" [13,14]. The major challenges identified in previous investigations of children's web search include spelling, typing, and query formulation [10,11].…”
Section: Children's Informational Query Practicesmentioning
confidence: 99%